Analisis Studi Literatur Kandungan Zat Berbahaya Pada Kosmetik Perawatan Kulit dan Rambut - Niken Ayu Saputri Ananda; Firdaus, Zahrotul; Elizabeth Serenity Johnree; Alfatia, Ainaya; Nadira Fathia Zulfa; Eny Widhia Agustin; Indah Indi Afifah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
With the development of the times, more and more people are more aware of their appearance. Using skin and hair care products is one way to support your appearance. Therefore, this study aims to analyze harmful substances that are often found in cosmetics, such as retinoic acid, hydroquinone, and Sodium Lauryl Sulfate (SLS), as well as examine their impact on health. Qualitative descriptive methods are used to analyze data from secondary sources, including scientific journals, government regulations, and related books. The results of the study show that retinoic acid, which is commonly found in acne ointments, has the potential to cause skin irritation and other health problems if not used under medical supervision. Hydroquinone, which is widely found in face lightening creams, although effective for brightening the skin, can cause risks such as ochronosis and irritation. SLS, which is widely used in cleaning products such as shampoo, can cause irritation in people with sensitive skin. In conclusion, the use of these ingredients should be done carefully and according to medical recommendations to avoid dangerous side effects. This study also suggests choosing products that are safer and do not contain these harmful ingredients.